Determinan Perilaku Merokok Pengunjung Kafe Di Kecamatan Lubuk Pakam - Sintia Safitri; Putra Apriadi Siregar (Preventia : The Indonesian Journal of Public Health, 2022)
AbstractSmoking is a habit that is widely practiced today by various groups. A total of 225,700 people died from smoking and other diseases caused by smoking in Indonesia. This study aims to determine the factors that most influence the smoking behavior of kafe visitors in Lubuk Pakam District. This research uses a combination research method (Mixed Method Research) with a Cross Sectional design. The data analysis technique used in this research is bivariate analysis. The results of this study indicate that there are 30 respondents (31.3 percent) who have smoking behavior and 66 respondents (68.8 percent) who do not have smoking behavior. Based on statistical tests, it was found that the variables related to the smoking behavior of the respondents were religious perspective on smoking law (p equal to 0.009), availability of cigarette ashtrays (p equal to 0.000), buying and selling cigarettes in kafes (p equal 0.000), family attitude (p equal 0.000) p equals 0.000), friends invite smoking (p equal 0.000), and cigarette advertisements (p equal 0.000). While the unrelated variables were religiosity (p equal to 0.160), smoker's family (p equal to 0.301) and the availability of air-conditioned rooms (p equal to 0.160). Based on the logistic regression test, it was found that the most influential variable on the smoking behavior of kafe visitors in Lubuk Pakam District was the availability of cigarette ashtrays at the kafe.Merokok merupakan sebuah kebiasaan yang banyak dilakukan pada saat ini oleh berbagai kalangan. Sebanyak 225.700 orang yang meninggal akibat merokok dan penyakit lainnya yang disebabkan oleh rokok di Indonesia. Penelitian ini bertujuan untuk mengetahui faktor yang paling mempengaruhi perilaku merokok pengunjung kafe di Kecamatan Lubuk Pakam. Penelitian ini menggunakan metode penelitian kombinasi (Mixed Method Research) dengan desain Cross Sectional. Teknik analisis data yang digunakan dalam penelitian ini adalah analisis bivariat. Hasil Penelitian ini menunjukkan terdapat 30 responden (31,3 persen) yang memiliki perilaku merokok dan 66 responden (68,8 persen) yang tidak memiliki perilaku merokok. Berdasarkan uji statistik didapatkan bahwa variabel yang berhubungan dengan perilaku merokok responden adalah cara pandang agama terhadap hukum rokok (p sama dengan 0,009), ketersediaan asbak rokok (p sama dengan 0,000), jual beli rokok di kafe (p sama dengan 0,000), sikap keluarga (p sama dengan 0,000), teman mengajak merokok (p sama dengan 0,000), dan iklan rokok (p sama dengan 0,000). Sedangkan variabel yang tidak berhubungan adalah religiusitas (p sama dengan 0,160), Keluarga perokok (p sama dengan 0,301) dan ketersediaan ruangan ber-AC (p sama dengan 0,160). Berdasarkan uji regresi logistik didapatkan bahwa variabel yang paling berpengaruh terhadap perilaku merokok pengunjung kafe di Kecamatan Lubuk Pakam adalah ketersediaan asbak rokok di kafe.